Use of Quranotherapy, a modality of transcendental meditation, for pain management in children: Uso de la Coranoterapia, una modalidad de meditación trascendental, para el manejo del dolor en niños - Caksen, Huseyin (2025)
There are many non-pharmacological therapies used to manage pain in children and that parents use non-pharmacological therapies than pharmacological therapies to manage their child's pain. Non-pharmacological therapies reduce the adverse events of drug use by contributing to the reduction of drug use and they may also improve the effectiveness of medications. Secondly, Quranotherapy, a transcendental meditation method, is effective in treating pain in both children and adults.